Diplomacy Beyond Language: François Guizot and Translation - Moyal, Gabriel (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractDiplomacy Beyond Language: François Guizot and Translation — Neglecting to mention translation, ignoring the need or even the presence of translation is common practice in non-literary French writing in the first half of the nineteenth century. Still, in the case of François Guizot (1787-1874) such neglect seems to have a more deliberate motivation. Before becoming prime minister of France or ambassador to England, Guizot had translated several important English texts into French. His later marginalization of linguistic difference appears more rooted in his ideological perspective on history. Guizot's writings on French and English history and on the evolution of language seem to indicate that, for him, in the long run of history, translation would become obsolete. Nations, like languages, appear, from his point of view, to be drifting towards an ultimate unity, to flow irresistibly towards a Utopian equality wherein differences — political or linguistic — will ultimately be dissolved.